Phylogenetic marker development for target enrichment from transcriptome and genome skim data: the pipeline and its application in southern African Oxalis (Oxalidaceae) - Schmickl, Roswitha; Liston, Aaron; Zeisek, Vojtěch; Oberlander, Kenneth; Weitemier, Kevin; Straub, Shannon C K; Cronn, Richard C; Dreyer, Léanne L; Suda, Jan (Molecular ecology resources, 2016)
Phylogenetics benefits from using a large number of putatively independent nuclear loci and their combination with other sources of information, such as the plastid and mitochondrial genomes. To facilitate the selection of orthologous low-copy nuclear (LCN) loci for phylogenetics in nonmodel organisms, we created an automated and interactive script to select hundreds of LCN loci by a comparison between transcriptome and genome skim data. We used our script to obtain LCN genes for southern African Oxalis (Oxalidaceae), a speciose plant lineage in the Greater Cape Floristic Region. This resulted in 1164 LCN genes greater than 600 bp. Using target enrichment combined with genome skimming (Hyb-Seq), we obtained on average 1141 LCN loci, nearly the whole plastid genome and the nrDNA cistron from 23 southern African Oxalis species. Despite a wide range of gene trees, the phylogeny based on the LCN genes was very robust, as retrieved through various gene and species tree reconstruction methods as well as concatenation. Cytonuclear discordance was strong. This indicates that organellar phylogenies alone are unlikely to represent the species tree and stresses the utility of Hyb-Seq in phylogenetics.
Keywords: genotypizační techniky; Sequence Analysis, DNA; jižní Afrika; Genetic Variation; Phylogeny; transkriptom; genetické markery; sekvenční analýza DNA; Transcriptome; fylogeneze; genom; genetická variace; Africa, Southern; Genome; Genotyping Techniques; Oxalidaceae; Genetic Markers